2008
DOI: 10.3168/jds.2008-1128
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Somatic Cell Score in Danish Holsteins Using a Liability-Normal Mixture Model

Abstract: Mixture models are appealing for identifying hidden structures affecting somatic cell score (SCS) data, such as unrecorded cases of subclinical mastitis. Thus, liability-normal mixture (LNM) models were used for genetic analysis of SCS data, with the aim of predicting breeding values for such cases of mastitis. Here, putative mastitis statuses and breeding values for liability to putative mastitis were inferred solely from SCS observations. In total, there were 395,906 test-day records for SCS from 50,607 Dani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 14 publications
3
17
2
Order By: Relevance
“…Using the same Bayesian approach, Penasa et al (2010) obtained a value of 0.05 for Table 1 Descriptive statistics for milk yield and somatic cell score both considering the whole sample and according to the health status (infected or not infected). the SCS heritability in a small autochthonous dairy cattle breed; whereas, other authors found higher values in German Holstein (Hinrichs et al, 2005) and Danish Holstein breed (Madsen and Odegard, 2006). The posterior mean estimate of heritability for liability to mastitis (i.e., infection status) was equal to 0.09, which is the same as the estimate reported by Riggio et al (2010) in a previous study on the same breed, using a threshold animal model, assuming a probit link function.…”
Section: Resultssupporting
confidence: 71%
“…Using the same Bayesian approach, Penasa et al (2010) obtained a value of 0.05 for Table 1 Descriptive statistics for milk yield and somatic cell score both considering the whole sample and according to the health status (infected or not infected). the SCS heritability in a small autochthonous dairy cattle breed; whereas, other authors found higher values in German Holstein (Hinrichs et al, 2005) and Danish Holstein breed (Madsen and Odegard, 2006). The posterior mean estimate of heritability for liability to mastitis (i.e., infection status) was equal to 0.09, which is the same as the estimate reported by Riggio et al (2010) in a previous study on the same breed, using a threshold animal model, assuming a probit link function.…”
Section: Resultssupporting
confidence: 71%
“…non-infected) and infected animals, is treated equally. However, several researchers suggested that, in cattle, SCS in healthy and infected animals are different traits (Detilleux and Leroy, 2000;Boettcher et al, 2007;Madsen et al, 2008). This was also confirmed in sheep by Riggio et al (2010), who showed that SCS in healthy and infected animals can indeed be considered as different traits-with different heritabilities, and with a genetic correlation between bacteria negative and bacteria positive SCS of 0.62.…”
Section: Alternative Statistical Modelling For Scc/scssupporting
confidence: 49%
“…Kause et al (2005) found that the genetic correlation between BW and skeletal deformations changed from positive to negative when trout got older and more fish showed skeletal deformations. Further, several studies indicated that somatic cell scores in healthy and infected cattle are genetically different traits (Boettcher et al, 2007;Madsen et al, 2008). When more energy is needed to overcome problems due to infections or metabolic disorders, less energy is available for production.…”
Section: Change Of Correlation Due To Ascites Incidencementioning
confidence: 98%